2010
DOI: 10.12991/201014453
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some novel hydrazone derivatives and evaluation of their antituberculosis activity

Abstract: INTRODUCTIONIn spite of a 5000 year history, tuberculosis (TB) remains the leading single-agent infectious disease killer in the world. Approximately one third of the world's population is infected with TB bacilli, and each year almost 8 million people develop active TB and 2 million die as a result of TB. The major challenges for tuberculosis control are the development of multidrug-resistant tuberculosis (MDRTB) strains and the increasing numbers of immunocompromised individuals with HIV infections who are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Hydrazidehydrazones and their derivatives are versatile molecules with broad spectrum biological activities (7)(8)(9)(10). Previously, we had synthesized a panel of flurbiprofen hydrazide-hydrazone derivatives and observed that they inhibited hepatitis C virus (HCV) NS5B RNA-dependent RNA polymerase (RdRp) activity by 20-50% at 200 μM concentration (11).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrazidehydrazones and their derivatives are versatile molecules with broad spectrum biological activities (7)(8)(9)(10). Previously, we had synthesized a panel of flurbiprofen hydrazide-hydrazone derivatives and observed that they inhibited hepatitis C virus (HCV) NS5B RNA-dependent RNA polymerase (RdRp) activity by 20-50% at 200 μM concentration (11).…”
Section: Introductionmentioning
confidence: 99%
“…During the coumarin-4-acetic acid benzylidene hydrazides as anti-TB agents against Mtb H37Rv strain, (7-Hydroxy-2-oxo-2H-chromen-4-yl)-acetic acid (3-nitro-benzylidene) hydrazide [38] was found to be most potent (Manvar et al, 2008). Some 5, 6, 7, 8-tetrahydronaphthalen acetic acid benzylidene hydrazide derivatives showed anti-TB activity and compounds having -OH and -NO 2 in ortho and Meta position of aromatic ring having high anti-TB activity (Ozemir et al, 2010). Aryl acetic acid hydrazones showed moderate activity against Mtb H37 RV strain (Srivastava et al, 2010).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The anticonvulsant potential of some hydrazone derivatives [91], [92] having long duration of action and a rapid onset of action (Kaushik et al, 2010). Antidepressant activity of hydrazones [93] has been reported (de Oliveira et al, 2011). The in-vitro β-amyloid aggregation inhibitory activity showed by hydrazone derivatives [96] with an IC 50 of 23μM (Catto et al, 2010).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Treatment options for these infections are often limited, especially in debilitated and immunocompromised patients. AhmetOzdemir et al (2010) synthesized some novel hydrazone derivatives by the reaction of (5,6,7,8-tetrahydronaphalen-1-yl) acetic acid hydrazide with various benzaldehydes which gave 5,6,7,8-tetrahydronaphthalen acetic acid benzylidenehydrazide derivatives and evaluated their antituberculosis activity which showed that compounds having -OH and -NO2 in ortho and meta position of aromatic ring having high antituberculosis activity and low cytotoxicity 27 . SrivsatavaRitu et al (2010) synthesized twelve aryl acetic acid hydrazonesand tested first time for their activity against mycobacterium.…”
Section: Antimicrobial Activitymentioning
confidence: 99%